2013
DOI: 10.1523/jneurosci.2425-13.2014
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Transplants of Human Adipose-Derived Stem Cell Protect the Brain from Traumatic Brain Injury-Induced Neurodegeneration and Motor and Cognitive Impairments: Cell Graft Biodistribution and Soluble Factors in Young and Aged Rats

Abstract: Traumaticbraininjury(TBI)survivorsexhibitmotorandcognitivesymptomsfromtheprimaryinjurythatcanbecomeaggravatedovertimebecauseof secondary cell death. In the present in vivo study, we examined the beneficial effects of human adipose-derived stem cells (hADSCs) in a controlled cortical impact model of mild TBI using young (6 months) and aged (20 months) F344 rats. Animals were transplanted intravenously with 4 ϫ 10 6 hADSCs (Tx), conditioned media (CM), or vehicle (unconditioned media) at 3 h after TBI. Significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
125
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(132 citation statements)
references
References 67 publications
0
125
0
2
Order By: Relevance
“…Considering the massive secondary cell death mediating the progression of TBI, novel treatments have been fashioned to target the delayed therapeutic time window post-TBI referred to as "neuroregeneration" in contrast to the narrow "neuroprotection" window relegated to the acute TBI phase (71,109). A major component of regenerative medicine is stem cell-based therapeutics, which have shown promising therapeutic potential for various types of neurological disorders, including TBI (e.g., 57,58,62,109,130), and have reached limited clinical trials [for review see (43)].…”
Section: Stem Cell Transplantation In Tbimentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the massive secondary cell death mediating the progression of TBI, novel treatments have been fashioned to target the delayed therapeutic time window post-TBI referred to as "neuroregeneration" in contrast to the narrow "neuroprotection" window relegated to the acute TBI phase (71,109). A major component of regenerative medicine is stem cell-based therapeutics, which have shown promising therapeutic potential for various types of neurological disorders, including TBI (e.g., 57,58,62,109,130), and have reached limited clinical trials [for review see (43)].…”
Section: Stem Cell Transplantation In Tbimentioning
confidence: 99%
“…A major component of regenerative medicine is stem cell-based therapeutics, which have shown promising therapeutic potential for various types of neurological disorders, including TBI (e.g., 57,58,62,109,130), and have reached limited clinical trials [for review see (43)]. Translating cell therapy for treatment of brain diseases to the clinic has involved testing the safety, efficacy, and mechanisms of action of a variety of transplantable donor cells, including fetal stem cells, cancer-derived neuron-like cells, embryonic stem cells, induced pluripotent stem cells, and adult stem cells, such as umbilical cord blood, bone marrow stromal cells, amnion cells, among others (16,57,58,62,63,74,75,84,87,90,109,130). However, among these various types of stem cells, adult stem cells are of interest, as they circumvent ethical and moral problems and also teratogenic and oncogenic risks usually associated with transplantation of embryonal or fetal-derived stem cells (85).…”
Section: Stem Cell Transplantation In Tbimentioning
confidence: 99%
“…Traumatic brain injury (TBI) is an acute intracranial injury caused by a sudden external force that may lead to brain concussion, contusion/laceration, bleeding, neurological dysfunction, and even death [1]. The prognosis and outcome of TBI is closely associated with the occurrence and existence of extracranial complications besides neurotrauma [2].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple sclerosis (MS), also known as disseminated sclerosis or encephalomyelitis disseminate, is an inflammatory disease (48). Previous studies have demonstrated the potential of stem cell-based MS therapy in autoimmune and cuprizone models of MS (49 -51).…”
Section: Multiple Sclerosismentioning
confidence: 99%